A data interchange standard for clinical neurophysiology. - Jacobs, E. C. (American Medical Informatics Association, 1993)
A Standard Specification for Transferring Digital Neurophysiological Data Between Independent Computer Systems (Designation E 1467-92) has been developed. The specification defines a common representation of all of the data associated with a complete clinical study, including digitized neurophysiological waveforms, textual annotations and interpretive reports. Patterned after existing, related healthcare data interchange standards, it will facilitate data interchange between neurophysiological instruments, computer systems within the neurophysiology laboratory, other information systems in the hospital, and outside healthcare facilities or research laboratories.